Mechanisms of ferroptosis and the relationship between ferroptosis and ER stress after JEV and HSV infection - Zhou, Rui; Wei, Kexin; Li, Xinyu; Yan, Beibei; Li, Lin (Frontiers in Microbiology, 2024)
Ferroptosis is a novel form of programmed cell death, which is different from apoptosis, pyroptosis and autophagy in morphology and biochemistry. Ferroptosis is characterized by condensed mitochondrial membrane densities, vanished of mitochondria crista and outer membrane rupture in morphology, and the accumulation of intracellular iron, lipid peroxidation, decrease of GSH and inhibition of GPX4 in biochemistry. Japanese encephalitis virus (JEV) and Herpes simplex virus (HSV) are both common neurotropic viruses that can cause neurological disorders, such as severe encephalitis. JEV and HSV have been demonstrated to be able to induce ferroptosis. This process is closely related to the inhibition of the GSH-GPX4 system, ACSL4 phosphorylation, and Nrf2 ubiquitination. In this review, we summarized the mechanisms by which JEV and HSV induce ferroptosis in the current study. In addition, we found a strong relationship between endoplasmic reticulum stress and ferroptosis, and We therefore speculated that sustained ER stress might be a prerequisite for ferroptosis in JEV and HSV-induced diseases.